Hyperbolic Traveling Wave Solutions for Sawada–Kotera Equation Using (??/???)-Expansion Method - Durur, Hülya; Yokuş, Asıf (My University, 2019)
In this study, we obtain hyperbolic traveling wave solutions of the Sawada–Kotera equation (S-K), using(1/???)-expansion methods. Special values are given to the parameters in the solutions obtained andgraphs are drawn. These graphs are presented using a computer package program. In this paper, (1/???)-expansion method is applied to reach the goals set. (1/???)-expansion method is an effective andpowerful method to obtain the traveling wave solutions of nonlinear partial differential equations.
Keywords: Matematik; Bilgisayar Bilimleri; Teori ve Metotlar